2013
DOI: 10.1002/lt.23649
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography for the detection of portopulmonary hypertension in liver transplant candidates: An analysis of cutoff values

Abstract: Portopulmonary hypertension (POPH), a complication of chronic liver disease, may be a contraindication to liver transplantation (LT) because of the elevated risk of peritransplant and posttransplant morbidity and mortality. Because POPH is frequently asymptomatic, screening with echocardiography is recommended. The only reliable technique, however, for diagnosing POPH is right heart catheterization (RHC). The aims of this study were to evaluate the current estimated systolic pulmonary artery pressure (sPAP) cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 34 publications
0
82
0
3
Order By: Relevance
“…If RV dilatation was added to this variable, then the sensitivity remained acceptable, and the specificity and PPV improved to 92% and 41%, respectively. 66,67 A right heart catheterization is extremely important in differentiating POPH from hyper dynamic state because of liver disease and volume overload ( Table 3). When the mPAP is higher than 25 mm Hg, with a pulmonary capillary wedge pressure (PCWP) lower than 15 mm Hg and PVR higher than 240 dyn/s/cm À5 , then in the right clinical setting the diagnosis of POPH can be made.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…If RV dilatation was added to this variable, then the sensitivity remained acceptable, and the specificity and PPV improved to 92% and 41%, respectively. 66,67 A right heart catheterization is extremely important in differentiating POPH from hyper dynamic state because of liver disease and volume overload ( Table 3). When the mPAP is higher than 25 mm Hg, with a pulmonary capillary wedge pressure (PCWP) lower than 15 mm Hg and PVR higher than 240 dyn/s/cm À5 , then in the right clinical setting the diagnosis of POPH can be made.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…TTE was noted to have a 97 % sensitivity and 77 % specificity to detect moderate to severe PAH prior to LT (Kim et al 2000). Based on different RVSP cutoffs, others have recommended that LT candidates with an RVSP > 38 mmHg should be referred for RHC (Raevens et al 2013a). More recently, the measurement of the main pulmonary artery diameter by computed tomography combined with echocardiography improved the accuracy in the diagnosis of POPH (Devaraj et al 2014).…”
Section: Screening For Pophmentioning
confidence: 98%
“…However, recent data on 152 patients undergoing pre-transplant echocardiography showed that a cutoff value of 30 mm Hg is associated with a specificity of 54%, resulting in unnecessary right-heart catheterizations, while a cutoff of 38 mm Hg yields a specificity of 82% and a sensitivity of 100%. 31 …”
Section: Pulmonary Manifestations Of Liver Diseasementioning
confidence: 99%
“…The optimal timing of such TTE screening has not been defined, although most centers perform yearly TTEs to identify patients with echocardiographic parameters suggestive of PAH. 31 Furthermore, the performance of routine TTEs can identify patients with cirrhotic cardiomyopathy complicated by decreased left- and/or right-ventricular systolic function. Despite the sensitivity however of TTE to identify depressed cardiac function which places patients at risk of overt heart failure post-transplantation, there still is a risk for post-operative heart failure despite a normal pre-transplant TTE.…”
Section: Cardiac Manifestations Of Liver Diseasementioning
confidence: 99%